TKN3 affects cell expansion to regulate fruit development in tomato - Shuai Sun; Yaqin Yuan; Meng Xu; Zhiqiang Liu; Xiaowei Yuan; Xingsheng Li; Ren Li; Xia Cui (Horticultural Plant Journal)
Tomato is a model system for studying fleshy fruit development. After fertilization, cell division and expansion in the pericarp are crucial for fruit development and determine the final fruit size. TKN3 was found to be expressed in the tomato ovary wall/pericarp of zero to two days post-anthesis fruits as a KNOX I class member, but its function in fruit development was elusive. Here, we found that mutations of TKN3 by CRISPR/Cas9 caused fruit developmental defects, and fruit weight was dramatically reduced in the tkn3cr mutant. Histological observation of fruit pericarps revealed that mutation of TKN3 repressed cell expansion after fertilization, leading to flattened cells in the mesocarp and thereby thinner pericarps in red fruits. Moreover, tkn3cr mutants also displayed pleiotropic phenotypes including enlarged leaves and floral organs, indicating conserved functions in meristem maintenance and leaf development. Yeast two-hybrid and BiFC assays further showed that TKN3 could interact with Solyc10g086640 (a homolog of Arabidopsis PNY), which has a similar expression pattern as TKN3. Genome-wide identification of genes regulated by TKN3 indicated that the auxin and gibberellin (GA) pathways might mediate the function of TKN3. Our works revealed that TKN3 controls cell expansion in pericarps, and provides new insights into the roles of KNOX proteins in fruit development.